Case report of successful live birth in an infertile couple with male idiopathic hypogonadotropic hypogonadism/azoospermia and atypical polypoid adenomyoma of the uterus - K. Okuno; K. Kitaya; N. Kim; K. Yamaguchi; H. Matsubayashi; T. Ishikawa (Clinical and Experimental Obstetrics & Gynecology)
The authors report a unique case of a successful live birth in an infertile couple both with male factor (idiopathic hypogonadotropic hypogonadism, IHH/azoospermia) and female factor [atypical polypoid adenomyoma (APA) of the uterus]. According to the history of ejaculation disorder and low values of serum follicle stimulating hormone, luteinizing hormone, and testosterone concentration, an infertile man was diagnosed with IHH. Gonadotropin therapy failed to produce ejaculated spermatozoa, but microdissection testicular sperm extraction was successful for retrieval and cryopreservation of motile testicular spermatozoa. Meanwhile, in the course of infertility workup for his female partner, fluid hysteroscopy detected multiple endometrial polypoid lesions in her uterine cavity. Hysteroscopic resection and histopathologic examinations revealed that the lesions were APA. Repeated hysteroscopic and histopathologic examinations did not find any evidence of the recurrence. She underwent controlled ovarian stimulation, oocyte pickup, and intracytoplasmic sperm injection using thawed testicular spermatozoa. She had a pregnancy in the first frozen-thawed blastocyst transfer cycle and gave birth to a healthy baby.